Conhecimento prévio, intertextualidade e pressuposição na leitura de crônicas - Santos, Cláudia Cristina Mário dos (2007)
The present dissertation is situated in the line of research Escrita e Ensino de Língua Portuguesa and its theme is the construction of meanings for the chronicle reading, investigating the importance, for this process, of the previous knowledge, of the beginning of Intertextuality and of the presupposed contents. Starting from the presupposed that such elements form strategies which facilitate the construction of meanings for the reading, and having as corpus four chronicles, the essay s objective was the carrying out of a study about the Intertextuality, the previous knowledge and the presupposed contents in this sort of text. The essay justified itself by the importance confronted by the PCN to the work with diversity of textual kinds, among which we spotted one chronicle, focusing the active reader s participation, emphasizing the formation of a critic reader accordingly the PCN suggest. In order to develop the essay the base was textual linguistics, especially the studies of Beaugrande & Dressles (1981), Beaugrande (1987), van Dijk (2002) and Koch & Travaglia (2003); also the postulates of Ducrot (1977; 1980; 1987) concerning the presumption concept. A methodology applied on the corpus consisted in identifying the elements which institute the relation between text and reader, analyzing how they act in the construction of the meanings. Therefore, at first we establish the analysis categories, considering the three general elements, previous knowledge, Intertextuality and presupposed contents. Afterwards, we identify these elements in the corpus and, then, we analyze them, verifying what their function in the construction of the meanings of the elected texts is. The carried out research made it possible to explore the previous knowledge demanded by the chronicles, the beginning of Intertextuality and the presupposed contents, evidencing that these phenomena constitute important strategies for the construction of the meanings in the reading of chronicles